Is listening to fat talk the same as participating in fat talk?. Issue 2 (15th March 2017) - Lin, Linda; Soby, Meghann
ABSTRACT: Our study examined whether verbally participating in fat talk conversations had a different effect on women's body image perception than merely listening to friends engage in fat talk conversations. Participants were 321 women who completed measures of listening to and participating in fat talk conversations, drive for thinness, body dissatisfaction, and dietary restraint. Results indicated that verbally participating in fat talk was a much stronger predictor of women's drive for thinness, body dissatisfaction, and dietary restraint than merely listening to friends engage in fat talk conversations.